Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Pada Perusahaan Asuransi (Studi Kasus: Pada Produk Asuransi Usaha Tani Padi (AUTP) PT. Asuransi Jasa Indonesia (Jasindo) Cabang Bandar Lampung Periode (2020-2022) - Sari, Murni Indah; Luthfi, Muhammad (Universitas Malahayati, 2024)
Agricultural insurance is a form of protection for farmers, through an agreement between farmers and insurance companies to commit to providing risk compensation for agricultural businesses, especially rice cultivation. This research method uses a quantitative method using primary and secondary data obtained from the company PT. Indonesian Services Insurance (Jasindo) Bandar Lampung Branch. This data analysis uses multiple linear regression analysis with a statistical approach, namely SPSS, by carrying out classic assumption tests, namely normality test, multicollinearity test, autocorrelation test and hypothesis testing, namely partial test (t test), simultaneous test (F test), and coefficient test. determination (R2). Based on the research results that have been tested, it can be concluded that the Rice Farming Business Insurance Premium Income variable (X1) has a partially positive and significant effect on the Financial Performance of PT. Asuransi Jasa Indonesia Bandar Lampung Branch (Y). The Premium Growth Variable (X2) of Rice Farming Business Insurance has a positive but not significant effect on the Financial Performance of PT. Asuransi Jasa Indonesia Bandar Lampung Branch (Y). The Claim Expense variable (X3) has a partially significant positive effect on the Financial Performance of PT. Asuransi Jasa Indonesia Bandar Lampung Branch (Y). The Own Retention Variable (X4) has a negative and partially significant effect on PT's Financial Performance. Asuransi Jasa Indonesia Bandar Lampung Branch (Y).